Heterogeneity of pollen food allergy syndrome in seven Southern European countries: The @IT.2020 multicenter study. Issue 10 (18th July 2021) - Lipp, Theresa; Acar Şahin, Aydan; Aggelidis, Xenophon; Arasi, Stefania; Barbalace, Andrea; Bourgoin, Anne; Bregu, Blerina; Brighetti, Maria Antonia; Caeiro, Elsa; Caglayan Sozmen, Sule; Caminiti, Lucia; Charpin, Denis; et al.
Abstract: Background: Pollen food allergy syndrome (PFAS) is a frequently underdiagnosed disease due to diverse triggers, clinical presentations, and test results. This is especially relevant in geographic areas with a broad spectrum of pollen sensitization, such as Southern Europe. Objectives: To elucidate similarities and differences of PFAS in nine Southern European centers and identify associated characteristics and unique markers of PFAS. Methods: As part of the @IT.2020 Multicenter Study, 815 patients with seasonal allergic rhinitis (SAR), aged 10–60 years, were recruited in seven countries. They completed questionnaires regarding SAR, comorbidities, family history, and PFAS, and underwent skin prick testing (SPT) and serum IgE testing. Results: Of the 815 patients, 167 (20.5%) reported PFAS reactions. Most commonly, eliciting foods were kiwi (58, 34.7%), peach (43, 25.7%), and melon (26, 15.6%). Reported reactions were mostly local (216/319, 67.7%), occurring within 5 min of contact with elicitors (209/319, 65.5%). Associated characteristics included positive IgE to at least one panallergen (profilin, PR‐10, or nsLTP) ( p = 0.007), maternal PFAS (OR: 3.716, p = 0.026), and asthma (OR: 1.752, p = 0.073). Between centers, heterogeneity in prevalence (Marseille: 7.5% vs. Rome: 41.4%, p < 0.001) and of clinical characteristics was apparent. Cypress played a limited role, with only 1/22 SPT mono‐sensitized patients reporting a food reaction ( p < 0.073). Conclusions: PFAS is a frequent comorbidity in Southern European SAR patients. Significant heterogeneity of clinical characteristics in PFAS patients among the centers was observed and may be related to the different pollen sensitization patterns in each geographic area. IgE to panallergen(s), maternal PFAS, and asthma could be PFAS‐associated characteristics. Abstract : In Southern Europe, there is a high heterogeneity in clinical characteristics of pollen food allergy syndrome among patients with seasonal allergic rhinitis. Patients frequently report reactions to kiwi, peach, and melon. Most patients report early localized reactions. The map was created using mapchart.net. Abbreviations: ATH, Athens; IST, Istanbul; IZM, Izmir; MAR, Marseille; MES, Messina; PFAS, pollen food allergy syndrome; POR, Porto; ROM, Rome; SAR, seasonal allergic rhinitis; TIR, Tirana; VAL, Valencia